Minimal clinically important differences for patient-reported outcome measures of cough and sputum in patients with COPD - Rebelo, Patrícia (2020)
BACKGROUND: Cough and sputum are highly prevalent in patients with chronic obstructive pulmonary disease (COPD). Pulmonary rehabilitation (PR) has shown to be effective in managing these symptoms. However, the interpretation of the magnitude of PR effects is hindered by the lack of minimal clinically important differences (MCIDs). PURPOSE: This study established MCIDs for the Leicester cough questionnaire (LCQ) and the cough and sputum assessment questionnaire (CASA-Q), in patients with COPD after PR. PATIENTS AND METHODS: An observational prospective study was conducted in patients with COPD who participated in a 12-weeks community-based PR program. Anchor- (mean change, receiver operating characteristic curves and linear regression analysis) and distribution-based methods [0.5*standard deviation; standard error of measurement (SEM); 1.96*SEM; minimal detectable change and effect size] were used to compute the MCIDs. The anchors used were: i) patients and physiotherapists global rating of change scale, ii) COPD assessment test, iii) St. George's respiratory questionnaire and iv) occurrence of an exacerbation during PR. Pooled MCIDs were computed using the arithmetic weighted mean (2/3 for anchor- and 1/3 for distribution-based methods). RESULTS: Forty-nine patients with COPD (81.6% male, 69.8±7.4years, FEV150.4±19.4%predicted) were used in the analysis. The pooled MCIDs were 1.3 for LCQ and for CASA-Q domains were: 10.6 - cough symptoms; 10.1 - cough impact; 9.5 - sputum symptoms and 7.8 - sputum impact. CONCLUSION: The MCIDs found in this study are potential estimates to interpret PR effects on cough and sputum, and may contribute to guide interventions.